The effects on biomechanics of walking and balance recovery in a novel pelvis exoskeleton during zero-torque control. Issue 8 (20th December 2014) - Martelli, Dario; Vannetti, Federica; Cortese, Mario; Tropea, Peppino; Giovacchini, Francesco; Micera, Silvestro; Monaco, Vito; Vitiello, Nicola
SUMMARY: Fall-related accidents are among the most serious concerns in elderly people, amputees and subjects with neurological disorders. The aim of this paper was to investigate the behaviour of healthy subjects wearing a novel light-weight pelvis exoskeleton controlled in zero-torque mode while carrying out unperturbed locomotion and managing unexpected perturbations. Results showed that the proposed exoskeleton was unobtrusive and had a minimum loading effect on the human biomechanics during unperturbed locomotion. Conversely, it affected the movement of the trailing leg while subjects managed unexpected slipping-like perturbations. These findings support further investigations on the potential use of powered exoskeletons to assist locomotion and, possibly prevent incipient falls.